Effective multi-unit leadership : local leadership in multi-site situations - Edger, Chris (Gower ; Ashgate, 2012)
Land-based multi-unit service enterprises face significant economic disruption at the present time. A pivotal actor in these organisations is the Multi-Unit Leader (MUL) - otherwise known as District, Area or Regional Manager. Given inherent challenges and their complex positional space, how do effective MULs optimise performance? In his book, Effective Multi-Unit Leadership - full of up-to-date case studies - Chris Edger advances an Integrated Model of MUL that elucidates how key activities (sales-led service, systems and standards - 3Ss) are driven through behavioural practices (commitment,